A novel FPGA architecture supporting wide, shallow memories. - Oldridge, S.W (IEEE Transactions on VLSI systems)
This paper investigates an architecture designed to implement wide, shallow memories on a field programmable gate array (FPGA). In the proposed architecture, existing configuration memory normally used to control the connectivity pattern of the FPGA is made user accessible. Typically, not all the switch blocks in an FPGA are used to transport signals. By adding only a modest amount of circuitry, the configuration memory in these unused switch blocks (or unused paths within used switch blocks) can be used to implement wide, shallow buffers and other similar memory structures. The size of FPGA required to implement a benchmark circuit that makes use of the wide, shallow memories, is 20% smaller than a standard memory architecture. In addition, the benchmark circuit is on average 40% faster using the proposed architecture.